2013
DOI: 10.1176/appi.ap.11030054
|View full text |Cite
|
Sign up to set email alerts
|

Nigerian Medical Students' Opinions About the Undergraduate Curriculum in Psychiatry

Abstract: Medical students surveyed would welcome an undergraduate curriculum that integrates the learning of psychiatry with other specialties and skills-training relevant for primary care. Efforts to modify the current curriculum in psychiatry in Nigerian medical schools should be encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A recent national survey of medical students showed that they did not see addiction psychiatry as relevant to their undergraduate psychiatry curriculum. 20 The training years for future physicians holds the best opportunity to correct misconceptions and promote positive attitudes regarding substance use and toward individuals who misuse them. Attitudes have been reported to become more negative as medical professionals transit through medical school and into a residency program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent national survey of medical students showed that they did not see addiction psychiatry as relevant to their undergraduate psychiatry curriculum. 20 The training years for future physicians holds the best opportunity to correct misconceptions and promote positive attitudes regarding substance use and toward individuals who misuse them. Attitudes have been reported to become more negative as medical professionals transit through medical school and into a residency program.…”
Section: Discussionmentioning
confidence: 99%
“…A recent national survey of medical students showed that they did not see addiction psychiatry as relevant to their undergraduate psychiatry curriculum. 20…”
Section: Discussionmentioning
confidence: 99%
“…The belief in heredity, genetic or biological factors was prevalent among medical doctors and medical students (Abayomi et al, 2013;Adewuya & Oguntade, 2007;Adewuya et al, 2017;Aghukwa, 2010;Igobodaro, 2017;Igobodaro, Stefanovics, Makanjuola & Rosenheck, 2015). Traditional or spiritual causation was prevalent among primary health care workers while medical doctors and medical students held more psychological and biological beliefs (Abiodun, 1991;Adelekan et al, 2001;Adewuya & Oguntade, 2007;Adewuya et al, 2017;Aghukwa, 2010;Ewhrudjakpo, 2009;Igbodaro et al, 2015;James, Lawani, Omoaregba & Jenkins, 2012;James et al, 2013). Two studies among traditional health practitioners showed that before training, the participants could not recognise symptoms of mental disorders and held a strong belief in supernatural causes such as actions from enemies using supernatural forces.…”
Section: Knowledge Perception and Views About The Causes And Treatment Of Mental Disorders In Nigeriamentioning
confidence: 99%
“…Some medical professionals expressed shame and were not willing to accept that a recovered mentally ill could teach children (Adewuya & Oguntade, 2007). However, more experienced medical health workers showed more positive attitude (James et al, 2013;Mosuku & Wallymahmed, 2016;Ogunlesi & Adelekan, 1988).…”
Section: Attitudes Towards People With Mental Disorders In Nigeriamentioning
confidence: 99%
“…In our centre, as in some other Nigerian universities, the clerkship is of only two weeks, running concurrently with a 16-week didactic lecture series by other subspecialties. Some researchers have recommended modifications to the current curriculum in psychiatry in Nigerian medical schools [15].…”
Section: Introductionmentioning
confidence: 99%